The Power of Local Language Terms in Creating Humor in English Language Teaching - Antonius Aliwutun; Iriany Kesuma Wijaya; M. Dahlan Bahang (Makassar State University, 2021)
Abstract. Humor is regarded as an important aspect in English language teaching (ELT). Therefore, English teachers are expected to create humors in their teaching. Creating humor in ELT, however, is still regarded hard for Many English language teachers. Humor is related to personal capability. Although humor has been widely explored, there is still scarcity on investigating it from local language terms. Therefore, this study came to investigate how humor can be presented in the classroom through local language terms. This was a descriptive qualitative study carried out at Pharmacology Institute of Makassar. The subjects of this study were students at the first semester that had different local languages. The data were collected through classroom observation and in-depth interview. This current study reveals that local language terms have significant power to present humor in ELT. Humor that created from local language input has emotional impact on cheerful learning in the classroom. The local language terms have power to trigger emotional engagement and enthusiasm in learning English. In addition, they function to reduce the complexity and anxiety in learning English as foreign language. Keywords: Local Language Terms, Humor, Emotional Engagement, Cheerful Learning.